Pengaruh Model Pembelajaran PAMER Berbantuan Video Animasi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Pancasila Di Kelas IV SD Negeri Gunung Sari II - Andi Arbaina Fariza; Andi Sugiati; Rismawati Rismawati (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research aims to determine the level of learning outcomes of students at SD Negeri Gunung Sari II in learning Pancasila Education after using the PAMER learning model assisted by animated videos and the influence of using the PAMER learning model assisted by animated videos on student learning outcomes in learning Pancasila Education for grade IV students at SD Negeri Gunung Sari II. This research uses the Quasi Experimental Design research method. The population in this study were all class IV students at SD Negeri Gunung Sari II. The sampling technique used was a total sampling technique or saturated sampling with experimental class and control class samples. The instrument used is a test instrument in the form of multiple choice questions to measure student learning outcomes with Pretest - Posttest Control Group Design. Based on the research results, it shows that students' Pancasila Education learning outcomes after using the PAMER learning model assisted by animated videos in the experimental class obtained an average score of 87.8 in the high category and in the control class an average score of 71.1 was obtained in the low category. Meanwhile, the effect of using the PAMER learning model assisted by animated videos on student learning outcomes in Pancasila Education learning for fourth grade students at Gunung Sari II State Elementary School from the results of hypothesis management obtained Sig (2.Tailed) = 0.000, meaning that H0 is rejected because Sig (2.Tailed) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.715 > 0.05) with the results of the T test analysis, Sig < ttable or (0.715 < 1.746). So the use of the PAMER learning model assisted by animated videos on learning outcomes in Pancasila education learning for class IV students has an influence at SD Negeri Gunung Sari II.